2018
DOI: 10.3389/fnins.2018.00125
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aging on the Auditory System and Related Cognitive Functions: A Narrative Review

Abstract: Age-related hearing loss (ARHL), presbycusis, is a chronic health condition that affects approximately one-third of the world's population. The peripheral and central hearing alterations associated with age-related hearing loss have a profound impact on perception of verbal and non-verbal auditory stimuli. The high prevalence of hearing loss in the older adults corresponds to the increased frequency of dementia in this population. Therefore, researchers have focused their attention on age-related central effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(116 citation statements)
references
References 249 publications
(316 reference statements)
1
110
1
4
Order By: Relevance
“…One of the most significant developments in our knowledge of ARHL etiology over the last decade has been the emergence of hearing loss as a risk factor for developing dementia. A large number of studies have found a link between ARHL and cognitive decline, dementia, and Alzheimer's disease with the hearing loss predating and predicting subsequent clinical diagnosis of dementia Gurgel et al 2014;Wei et al 2017;Jayakody et al 2018). There are several possible explanations for this association between the two morbidities and the resulting implications for our understanding of the mechanisms underlying the two diseases.…”
Section: Arhl and Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most significant developments in our knowledge of ARHL etiology over the last decade has been the emergence of hearing loss as a risk factor for developing dementia. A large number of studies have found a link between ARHL and cognitive decline, dementia, and Alzheimer's disease with the hearing loss predating and predicting subsequent clinical diagnosis of dementia Gurgel et al 2014;Wei et al 2017;Jayakody et al 2018). There are several possible explanations for this association between the two morbidities and the resulting implications for our understanding of the mechanisms underlying the two diseases.…”
Section: Arhl and Dementiamentioning
confidence: 99%
“…Third, there may be common pathological pathways involved in causing both disorders. Plausible pathways that have been linked to both pathologies include oxidative damage, inflammation, vascular function, mitochondrial dysfunction, glutamate excitotoxicity, and RNA granule dysregulation (Towers et al 2011;Wong and Ryan 2015;Ganguly et al 2017;Maziuk et al 2017;Du et al 2018;Jayakody et al 2018;Ridge and Kauwe 2018). It is also possible that more than one of these models is relevant and that, as well as common causative factors underlying hearing loss and cognitive decline with age, the resulting lack of auditory input accelerates the psychological consequences and hence the clinical impact of the pathology.…”
Section: Age-related Hearing Lossmentioning
confidence: 99%
“…ARHI is characterised by a non-syndromic bilateral, sensorineural hearing loss that progresses with increasing age and is an established risk factor for depression [6][7][8] and dementia [9][10][11][12] . Hearing loss was ranked fourth in the latest study into the Global Burden of Diseases 13 , yet hearing amplification devices are the only treatment option currently available for ARHI.…”
Section: Age-related Hearing Impairment (Arhi) Is the Most Common Senmentioning
confidence: 99%
“…Nevertheless, sensory ageing is not homogeneous across sensory systems, and large differences exist among these systems (Andersen, ; Jayakody et al. ). The experimental and clinical findings regarding the ageing of the somatosensory system (involving mechanoreception, thermoreception and nociception) are not conclusive, probably because of the involvement of the central nervous system, the peripheral nervous system and skin (Shaffer & Harrison, ; Goble et al.…”
Section: Introductionmentioning
confidence: 99%